APPLICATION OF THE VISUALIZATION, AUDITORY, KINESTHETIC (VAK) MODEL TO STUDENT LEARNING OUTCOMES IN REGIONAL CREATIVE DANCE ART MATERIALS (TOP PADE DANCE) CLASS IV AT UPTD SPF SD NEGERI SUMBER MUKTI - Oktania, Ririn; Fitri, Aida; Mislinawati, Mislinawati (Universitas Syiah Kuala, 2025)
Most students do not understand learning, especially creative dance material. Students are not taught using practical methods but are only given theories by the teacher. The dance material taught by teachers focuses more on theory and some even skip this material. This results in the role of students becoming more passive in learning and not even knowing the learning material. The formulation of the problem in this research is